DESIGN MODELS FOR EMBEDDED SYSTEMS AND SENSOR NETWORKS - Karakehayov, Zdravko (International Journal of Computing, 2010)
This paper introduces a hierarchical design model for embedded systems which includes models of the application, the embedded system and the resources. The application model deals with locations to better describe distributed architectures. A location-driven method for design of distributed embedded systems is proposed as a direct extension of the design model. The method allows to benefit from fuzzy relationships between I/O variables and locations. An example shows a 29% reduction of the hardware complexity measured in number of pins. In case of wireless links the model allows sensor networks to gradually emerge as a class of embedded systems.